2016
DOI: 10.1017/s0022029915000709
|View full text |Cite
|
Sign up to set email alerts
|

Effects of α-linolenic acid-enriched diets on gene expression of key inflammatory mediators in immune and milk cells obtained from Holstein dairy cows

Abstract: Immune system and inflammatory responses are affected by α-linolenic acid (αLA: 18:3 ω-3). The objective of this study was to determine the effects of αLA-enriched rations on gene expression of systemic (blood) and local (mammary gland) inflammatory markers in Holstein dairy cattle. Further, the effect of dietary treatments was evaluated on the concentration of αLA in serum phospholipids. Camelina (Camelina sativa) meal (containing 24.2% αLA) was fed at 0, 3, 6, and 9% (dry matter basis) replacing canola meal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…Studies have demonstrated that feeding n-3 PUFA can decrease soluble TNF-α production in rodent macrophages as well as in equine and rats blood monocytes [24], which is similar with our results showing that the concentration of TNF-α in serum was decreased in n-3 PUFA enriched-oil feeding dairy cows. These results are also consistent with Rezamand et al [25] who reported that ALA-enriched diets could reduce the expression of pro-inflammatory markers TNF-α. Indeed, correlation analysis in the present study found that the content of n-3 PUFA (ALA) was negatively correlated with the concentrations of TNF-α in serum.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have demonstrated that feeding n-3 PUFA can decrease soluble TNF-α production in rodent macrophages as well as in equine and rats blood monocytes [24], which is similar with our results showing that the concentration of TNF-α in serum was decreased in n-3 PUFA enriched-oil feeding dairy cows. These results are also consistent with Rezamand et al [25] who reported that ALA-enriched diets could reduce the expression of pro-inflammatory markers TNF-α. Indeed, correlation analysis in the present study found that the content of n-3 PUFA (ALA) was negatively correlated with the concentrations of TNF-α in serum.…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have reported that PUFA plays a key role in modulation of the immune system and inflammatory responses (37). Rezamand et al reported that α-linolenic acidenriched diets down-regulated expression of IL-6 and IL-8 pro-inflammatory factors (38). In our study, we found that eicosapentaenoic acid and adrenic acid significantly negatively correlated with inflammatory factors, but 16-hydroxypalmitic significantly positively correlated with inflammatory factors.…”
Section: Discussionsupporting
confidence: 55%
“…Pro-inflammatory and bioactive eicosanoids can be derived from LA 14 . α-LA has been shown an anti-inflammatory effect 15 , studies showed that increasing α-LA in diets can reduce the expression of the pro-inflammatory cytokine TNF-α, and the secretion of IL-1 16 . In the present study, there were significant reductions in α-LA and LA in LPS12h ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%